2023
DOI: 10.1136/bmj-2022-072924
|View full text |Cite
|
Sign up to set email alerts
|

Ionising radiation and cardiovascular disease: systematic review and meta-analysis

Abstract: ObjectiveTo systematically review and perform a meta-analysis of radiation associated risks of cardiovascular disease in all groups exposed to radiation with individual radiation dose estimates.DesignSystematic review and meta-analysis.Main outcome measuresExcess relative risk per unit dose (Gy), estimated by restricted maximum likelihood methods.Data sourcesPubMed and Medline, Embase, Scopus, Web of Science Core collection databases.Eligibility criteria for selecting studiesDatabases were searched on 6 Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 94 publications
1
84
0
4
Order By: Relevance
“…As long as uniform incidence ascertainment is made, incidence data are more reliable and preferable than mortality data, and for this aim, disease assignment plays a pivotal role. The latest systematic review of epidemiological literature published by October 2022 and its meta-analysis (hereafter referred to as the latest meta-analysis) documented that there were indications of a DCS risk for mortality with a metaanalysis ERR (mERR)/Gy of 0.20 (95% CI: 0.13, 0.26) higher than that for incidence with 0.09 (95% CI: 0.05, 0.13) when estimated from all relevant studies: there were similar (but nonsignificant) indications when restricted to high quality studies (120). In the Mayak studies, a difference between incidence and mortality is evident, but in an opposite way, which have shown increased risks for incidence of various DCS subtypes (i.e., IHD, angina pectoris, heart failure and CeVD in both sexes, cardiac arrhythmia and conduction disorder in males, but not acute myocardial infarction and stoke in both sexes, nor cardiac arrhythmia and conduction disorder in females) but for mortality of only ischemic stroke in men within the resident subcohort (123,140).…”
Section: Mortality Incidence Disease Ascertainment and Diagnosis Cate...mentioning
confidence: 94%
See 1 more Smart Citation
“…As long as uniform incidence ascertainment is made, incidence data are more reliable and preferable than mortality data, and for this aim, disease assignment plays a pivotal role. The latest systematic review of epidemiological literature published by October 2022 and its meta-analysis (hereafter referred to as the latest meta-analysis) documented that there were indications of a DCS risk for mortality with a metaanalysis ERR (mERR)/Gy of 0.20 (95% CI: 0.13, 0.26) higher than that for incidence with 0.09 (95% CI: 0.05, 0.13) when estimated from all relevant studies: there were similar (but nonsignificant) indications when restricted to high quality studies (120). In the Mayak studies, a difference between incidence and mortality is evident, but in an opposite way, which have shown increased risks for incidence of various DCS subtypes (i.e., IHD, angina pectoris, heart failure and CeVD in both sexes, cardiac arrhythmia and conduction disorder in males, but not acute myocardial infarction and stoke in both sexes, nor cardiac arrhythmia and conduction disorder in females) but for mortality of only ischemic stroke in men within the resident subcohort (123,140).…”
Section: Mortality Incidence Disease Ascertainment and Diagnosis Cate...mentioning
confidence: 94%
“…Accumulating evidence has supported increased radiation risks for DCS, especially ischemic heart disease (IHD) and CeVD at high dose, and to a lesser extent at low dose, albeit with interstudy heterogeneity (117)(118)(119)(120). At similar levels of cumulative dose posed by protracted exposure, however, increased radiation risks for DCS mortality have been observed in the International Nuclear Workers Study (INWORKS, the joint analysis of cohorts in France, UK and US) (121) cohort, but not in any cohorts of the US Million Person Study (MPS) (122).…”
Section: Manifestations and Dose Thresholdsmentioning
confidence: 99%
“…La radiación ionizante tiene efectos carcinógenos, y se ha relacionado con mayor riesgo de cánceres ocupacionales como mesotelioma (Visci et al, 2022), cáncer de mama y tiroides (Gonzalez et al, 2020) y cáncer de piel no melanoma (Azizova et al, 2018). La exposición ocupacional afecta las hormonas tiroideas y se relaciona con una mayor probabilidad de desarrollar enfermedades inmunes tiroideas (El-Benhawy et al, 2022) y enfermedad cardiovascular (Little et al, 2023).…”
Section: Fuente: Elaborada Por El Autorunclassified
“…In a linked BMJ article (doi:10.1136/bmj-2022-072924),1 Little and colleagues report the results of a large meta-analysis of 93 studies evaluating associations between a range of cardiovascular diseases and exposure to radiation in various settings (mostly radiotherapy and occupational exposures, but also diagnostic radiology and environmental exposures). The authors found robust evidence for a dose dependent increase in cardiovascular risks across a broad range of radiation doses.…”
mentioning
confidence: 99%
“…Cancer risk is the most important health risk related to low dose radiation because the risk coefficients per dose unit are lower for cardiovascular disease than for cancer (excess relative risk per grey around 0.1-0.2 v 0.4-0.5) 111. Nevertheless, absolute cardiovascular risks attributable to radiation per dose unit are not materially lower than those for cancer risks because of the high baseline risks of cardiovascular disease.…”
mentioning
confidence: 99%